2011 IEEE Symposium on Computers and Communications (ISCC) 2011
DOI: 10.1109/iscc.2011.5983882
|View full text |Cite
|
Sign up to set email alerts
|

Towards realization of the ABC vision: A comparative survey of Access Network Selection

Abstract: Access Network Selection (ANS) providing the most appropriate networking technology for accessing and using services in a heterogeneous wireless environment constitutes the heart of the overall handover management procedure. The aim of this paper is to survey representative vertical handover schemes proposed in related research literature with emphasis laid on the design of the ANS mechanism. Schemes' distinct features are analyzed and the authors discuss on their relative merits and weaknesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…This mobility support enables Always Best Connected (ABC) paradigm, which is important in UbiComp systems [Louta et al, 2011].…”
Section: Multihoming Evaluation Frameworkmentioning
confidence: 99%
“…This mobility support enables Always Best Connected (ABC) paradigm, which is important in UbiComp systems [Louta et al, 2011].…”
Section: Multihoming Evaluation Frameworkmentioning
confidence: 99%
“…More information on this general research problem can be found, e.g. from the survey papers [7][8][9][10][11][12]. The proposed algorithms are based on a multitude of different techniques, such as neural networks, reinforcement learning (RL), fuzzy logic, Bayesian network, game theory, multi-criteria decision-making and analytical hierarchical process.…”
Section: Related Workmentioning
confidence: 99%
“…There are many proposals proposed by researchers about ANS, e.g. [4,5]; however, the proposed ANS schemes lack unity, while a number of issues still need to be resolved such as the goals discrepancy between user centric and network centric, where in user centric scheme the goal is how to get best connection anywhere anytime regardless of network operation complexities associated with this which matters from operator's perspective [6]. Although there are many approaches that have been presented to provide seamless VHO [2,3,[11][12][13][14][15][16], we will consider three of them [3, 11 and 12] which have been evolved from each other such that the recent approach of them [3] combined between MIH and ANDSF mechanisms.…”
Section: Related Workmentioning
confidence: 99%